Studies of New Multistory House Electrical Supply Load and Determination Methods Update - Budahs, Martins; Vanzovichs, Edvins; Zviedritis, Mareks (Electrical, Control and Communication Engineering, 2010)
A large amount of work has devoted to electric supply system load determination. Most of the load calculation methods and values of the appropriate factors were found many years ago and are outdated, for example, electric supply system for new many dwelling houses. At this time, there is changed not only value of loads but also its character - thus leaving the impact on the calculation methodology and factors values.Employers of Latvenergo Distribution Network are realized wide range of load inspection in more then 24 commercial buildings and dwelling houses over two years. The results are presented in the form of official instruction. This paper is continuing the ongoing theme and dedicating improving possibilities of the calculation methodology. Particular attention has paid to existing methods of load calculation, physical interpretation of factors and possible character changes in the range.The method is designed for design engineers and engineering staff, working with the maintenance and control of apartment buildings.The methodology is not applicable in buildings with electric heating and hot water.